DIAGNOSTIC UTILITY OF MAJOR AND MINOR CLINICAL MANIFESTATIONS IN EARLY RHEUMATOID ARTHRITIS: A SEROLOGICAL AND PHENOTYPIC CORRELATION ANALYSIS (World Bulletin of Public Health, 2026)
The precise differentiation of early-stage rheumatoid arthritis from transient inflammatory arthropathies relies heavily on the rigorous systematic evaluation of established major and minor clinical diagnostic criteria. This study evaluates the specific predictive value and serological correlation of these articular and extra-articular manifestations in a treatment-naive cohort to optimize early pharmacological intervention. A prospective clinical analysis was conducted involving 126 adult patients presenting with undifferentiated polyarthritis and suspected early rheumatoid arthritis. Subjects were stratified based on their baseline serological profiles into an autoantibodypositive cohort (n=78, positive for Rheumatoid Factor and Anti-Cyclic Citrullinated Peptide) and a seronegative cohort (n=48). Clinical data indicate that isolated reliance on major criteria, such as radiographically confirmed erosions or classic symmetric polyarthritis of small joints, frequently delays the initiation of disease-modifying therapies. The autoantibody-positive cohort demonstrated a 92.3% prevalence of prolonged morning stiffness exceeding 60 minutes and constitutional fatigue (minor criteria), which preceded the onset of palpable rheumatoid nodules or fixed joint deformities (major criteria) by an average of 4.2 ± 1.1 months. Conversely, the seronegative group exhibited a highly asymmetrical onset and a significantly lower incidence of systemic minor signs (p = 0.014). The dynamics of the observed results suggest that minor clinical manifestations are not merely secondary physiological phenomena but are critical, early indicators of aggressive autoimmune phenotyping. Comprehensive diagnostic protocols must actively integrate the systematic quantification of minor symptoms alongside serological markers to preemptively halt irreversible articular destruction before major classical criteria fully manifest.
Keywords: Clinical pharmacology; rheumatoid arthritis; major diagnostic criteria; minor clinical signs